Isocitrate dehydrogenase 1 mutation subtypes at site 132 and their translational potential in glioma - Victor M Lu; Kerrie L McDonald (CNS Oncology, 2018)
In recent years, de novo missense structural mutations in the IDH1 gene of arginine at site 132 (R132) have become a standard for diagnostication and prognostication in glioma management. As our clinical understanding of this mutation grows, so too does the number of mutation subtypes reported in the literature. By synergizing current knowledge of IDH1 activity in glioma with the emerging evidence of different enzyme kinetics between R132 IDH1 mutation subtypes, the translational potential in improving glioma management based on mutated IDH1 subtype in glioma is described.